The Types of Educational Comics and Analysis of Their Educational Potential for Science Instruction - Trnová, Eva; Janko, Tomáš; Trna, Josef; Pešková, Karolína (Scientia in educatione, 2016)
Traditionally, comics are perceived as a specific popular medium. Thanks to their popularity and understandability for adolescents, they are nowadays paid increasing attention even in the domain of science education. In this respect, an important aspect of the comics is their content as well as their means of expression. This study aims to explore the educational potential of the medium and to suggest ways of its beneficial educational use for the contemporary NET-generation of students. Based on the selected examples, educational comics are analyzed as means supporting the transformation of scientific educational concepts to a more understandable form. First, the reader is familiarized with the benefits of comics with respect to the educational needs of the current generation of students. Further, the qualities and functioning of comics as educational means are explained. Finally, recommendations for the effective use of comics in science instruction are suggested.